SUPPLEMENT OF NANOTECHNOLOGIES AND NANOMATERIALS - Sultanxodjayeva Gulnoza Shuxratovna; Maxmudova Dilafruz Xasanovna (Innovative Development in Educational Activities, 2023)
In this article, the theoretical and practical issues of the use of nanotechnology in solving the main problems of the energy sector and environmental protection were analyzed. Nanotechnology has a huge economic potential for use in all areas of energy, and it is said that it will help to increase efficiency and environmental cleanliness in all stages: in all types of energy sources, in the production, storage and transformation of energy, in its transmission and use